Percepción sobre la contaminación por residuos sólidos domiciliarios en la comunidad de Santo Tomás, distrito de Punchana, Loreto - Perú, 2022 - Rodriguez Reina, Leoncio Junior (2022)
The present work of thesis was developed in the Native Community of Saint Tomas situated to the right side of the Nanay river from the Nanay port of Iquitos City, the evaluation was realized during the months of May to September of 2022, and it had had as objective Know the perception of the population of the Native Community of Saint Tomas about the environmental problematic of the household solid, and to improve their segregation and disposal. Through the analysis and the processing of the information collected from the perception of the rural villager about the household solid waste generated in the Native Community of Saint Tomas, through the application of a survey, which covers the aspects of knowledge, awareness, management of household solid waste, cover valid information which contribute to plan proposes for a better gestion, segregation, disposal, sensibilization, and conscientization of household solid waste.